Construction of a Robust Sphingomonas sp. Strain for Welan Gum Production via the Expression of Global Transcriptional Regulator IrrE - Liu, Xiaoliu; Zhao, Ming; Xu, Zheng; Xu, Hong; Li, Sha (Frontiers in Bioengineering and Biotechnology, 2020)
Welan gum is a widely used microbial polysaccharide produced by Sphingomonas sp.. However, an important factor hindering the expansion of its production is the maladaptation of strain to fermentation conditions. In this work, the global transcriptional regulator gene irre was selected as a stress-resistant element. And it was integrated into the site of the genomic carotene synthesis key enzyme gene crtB to construct a robust carotenoid-free welan gum producing strain. Fermentation with the recombinant strain effectively reduced the ethanol consumption and pigment content in the product. The tolerance temperature increased by 10 °C without the need for controlling the pH. Under this fermentation condition, welan gum concentration could still reach 20.26 ± 0.25 g/L, which was 187.38% higher than that of the wild-type strain (7.05 ± 0.15 g/L). Transcriptome analysis showed that with the control of IrrE, more than 1000 genes that are involved in multiple pathways, including two-component system, bacterial chemotaxis, flagellar assembly, and cell cycle, exhibited changes at the transcriptional level and jointly allowed the strain to protect against environmental stresses.